2021
DOI: 10.1007/s00374-021-01597-7
|View full text |Cite
|
Sign up to set email alerts
|

Root and shoot growth of spring wheat (Triticum aestivum L.) are differently affected by increasing subsoil biopore density when grown under different subsoil moisture

Abstract: A column experiment with five different pore densities (0, 1, 2, 3, and 4 pores column−1) and two varying moisture regimes (comparatively dry and comparatively moist regime) in the subsoil part of the columns was established. In each pore, Lumbricus terrestris was introduced for 28 days before sowing wheat plants. After 40 days of plant growth, watering was stopped to induce progressive topsoil drying. Parameters describing the shoot hydration, mineral uptake, and aboveground biomass were quantified. Root biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Furthermore, Kautz (2015) reported that the density of biopores also had an important effect on crop growth. Under 30% water holding capacity, Koch et al (2021) found that the shoot biomass of wheat increased when the biopore density increased, but not for root biomass. At a given biopore diameter of 0.5 mm, Xiong, Zhang, Guo, et al (2022) reported that a biopore density of 7000 m -2 might better enhance maize root growth than biopore densities of 1750 and 28,000 m -2 in compacted soil.…”
Section: Root Growth Is Affected By Bioporesmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, Kautz (2015) reported that the density of biopores also had an important effect on crop growth. Under 30% water holding capacity, Koch et al (2021) found that the shoot biomass of wheat increased when the biopore density increased, but not for root biomass. At a given biopore diameter of 0.5 mm, Xiong, Zhang, Guo, et al (2022) reported that a biopore density of 7000 m -2 might better enhance maize root growth than biopore densities of 1750 and 28,000 m -2 in compacted soil.…”
Section: Root Growth Is Affected By Bioporesmentioning
confidence: 92%
“…Under 30% water holding capacity, Koch et al. (2021) found that the shoot biomass of wheat increased when the biopore density increased, but not for root biomass. At a given biopore diameter of 0.5 mm, Xiong, Zhang, Guo, et al.…”
Section: Root–biopore Interactionsmentioning
confidence: 99%
“…The effects of artificial pores on root growth of various of plants have been investigated intensively (Atkinson et al, 2020;Colombi et al, 2017;Koch et al, 2021;Pfeifer et al, 2014). Pfeifer et al…”
Section: Effects Of Artificial Pores On Maize Root Growthmentioning
confidence: 99%
“…Xiong, Zhang, Guo, et al (2022) found that for 0.5‐mm macropore, a medium density (20 macropores per column) improved maize root growth compared with low (5) and high (80) pore densities. Koch et al (2021) reported that a high artificial biopore density was helpful to improve the root and shoot growth of spring wheat, yet depends on subsoil water content. Although these studies provide important insights into pore‐root interactions, the artificial pores failed to represent old root channels accurately, because biochemical properties of the rhizosheath were not reproduced.…”
Section: Introductionmentioning
confidence: 99%
“…Subsoiling tillage [ST, usually combined with straw mulching (STSM)] plays important roles in agricultural production, especially in dryland regions, as it is able to increase rainfall harvest, crop yield, and efficiency ( Cai et al., 2014 ; Arnhold et al., 2023 ) and address environmental issues ( Zhao et al., 2023b ). Previous studies have primarily demonstrated that ST can influence crop growth and development by reducing soil bulk density ( Ahmad et al., 2009 ; Lampurlanés et al., 2016 ; Sun et al., 2018 ), increasing soil porosity ( Xue et al., 2018 ), enhancing water infiltration ( Liang et al., 2019 ; Qiang et al., 2022 ), increasing soil water usage ( Wang et al, 2022 ; Yang et al., 2022 ), optimizing soil physical properties and fertility ( He et al., 2019 ; Wang et al, 2020 ; Yang et al., 2022 ), improving root characteristics ( Izumi et al., 2009 ; He et al., 2019 ; Koch et al, 2021 ; Arnhold et al., 2023 ), enhancing tiller density ( Lv et al., 2019 ), delaying senescence ( He et al., 2020 ), promoting plant photosynthesis characteristics ( Sang et al., 2016 ; He et al., 2019 ), and facilitating dry matter accumulation and remobilization ( Zhang et al., 2023 ). In the Loess Plateau of China, studies of two 2-year experiments showed that ST during the summer fallow season improved soil nutrient characteristics, wheat growth, and N uptake characteristics, thus not only increasing wheat yield and water use efficiency (WUE), but also optimizing the quality of albumin, gliadin, glutenin, total protein, and sedimentation values and wet gluten contents ( Sun et al., 2013 ; Zhao et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%